The Fiscal Multiplier in Small Open Economy : The Role of Liquidity Frictions - Sin, Jasmin (IMF Working Papers; Working Paper ;, 2016)
This paper studies the fiscal multiplier using a small-open-economy DSGE model enriched with financial frictions. It shows that the multiplier is large when frictions are present in domestic and international financial markets. The reason is that in the model government bonds are more liquid than private financial assets and that entrepreneurs face liquidity constraints. A bond-financed fiscal expansion eases these constraints and stimulates investment and hence growth. This mechanism, however, breaks down under the assumption of perfect international capital mobility, suggesting that conventional models which ignore the presence of frictions in international capital markets tend to underestimate the fiscal multiplier.